Dysphonia as a manifestation of aortic aneurysm endoprosthesis leak: A case of Ortner´s syndrome - Vargas-Rubio, Víctor Alonso (2021)
We present the case of a 49-year-old man with a history of descending aortic aneurysm treated with endoprosthesis, who presented with dysphonia of two months of evolution as the main symptom. Nasolaryngoscopy and imaging study determine that the dysphonia is caused by a left vocal cord paralysis; when suspected of damage to the left recurrent laryngeal nerve, a chest tomography is performed that shows a residual aneurysm with endoprosthetic leakage, which explains the damage of this nerve. It is concluded in an Ortner syndrome as a manifestation of endoleaks.